(untitled) (Encuentros, 2025)
The objective of this article is to present the research results of the project entitled: “Pedagogical strategies in social sciences for the teaching and conservation of oral tradition and historical memory in the José Consuegra Higgins Educational Institution of the Isabel López district”, analyzing the representative elements of the oral tradition and historical memory of the town of Isabel López, product of the knowledge and wisdom of 192 students from sixth to tenth grade, from a dialogic, comprehensive, multidimensional, complex and human vision. The premise of a methodological proposal from complexity, visualized from the emerging paradigm, reflects an educational reality capable of breaking into the conception of the classroom not only as a physical learning space, linear and modeling knowledge, experiences or practices, towards an education in relation dialogic with interdisciplinary processes, this being an emerging scenario of knowledge and knowledge based on multiple theories, awareness and active participation, for purposes of reflection, training and transformation of the educational community. It is concluded that the oral tradition and the historical memory of the town of Isabel López are considered two key transversal axes of social development, as well as drivers of the curriculum, becoming pedagogical strategies that strengthen the teaching and learning of social sciences.